Pemetaan dan Alternatif Pemanfaatan Limbah Cangkang Rajungan di Indonesia: Mapping and Alternative Utilization of Shell Crab Waste in Indonesia - Kiki Puspita Amalia; Meti Ekayani; Nurjanah Nurjanah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Pasteurized crab meat is one of the largest fishery export commodities in Indonesia. Fish Processing Unit (FPU) receives raw materials in the form of whole crab from the miniplant, thus leaving a fairly large crab waste because about 50-60% of the crab is the shell. Previous research has informed that crab waste has potential utilization and it can increase the economic value of the crab waste. This study aims to map the supply chain related to the use of crab waste, including calculate waste potential, economic value and identify alternative uses of crab waste. The method used is a qualitative descriptive, benefit transfer, and income analysis. The result of this study represent supply chain mapping of crab waste utilization in 8 provinces based on 37 FPU and 148 miniplant on 9 provinces that supply raw materials. Based on the main choice of alternative utilization by respondents, the number of shells available in each province and the high economic value of chitosan, shell waste has great potential used as chitosan.